Understanding Accounting Practices in Culinary MSMEs In The Tanjung Bunga Metro Area, Makassar City - Saleh, Andi Mulia; Alimuddin; Said, Darwis (PT. Maju Malaqbi Makkarana, 2026)
The focus of research shifts from the dominance of positivism to a non-positivistic approach that places meaning, interpretation, and social construction at the center of analysis. One of the main approaches within this paradigm is Grounded Theory Research (GTR), a qualitative method developed by Glaser and Strauss (1967) to build empirically data-based theory through a rigorous inductive process. In the accounting context, GTR becomes increasingly relevant because reporting practices, accountability, and financial decision-making cannot be understood solely through objective measurements, but rather through social interactions, organizational values, and the interpretations of the actors involved (Ahrens & Chapman, 2006). This article aims to examine the role and relevance of GTR in modern accounting research by highlighting its philosophical foundations, methodological procedures, and contributions to the development of practice-based accounting theory. Through a systematic literature review, it is found that GTR has the ability to uncover the social dynamics that shape accounting practices such as accountability, ethics, managerial control, and institutional legitimacy that have previously been overlooked by positivistic approaches (Charmaz, 2006; Bryant & Charmaz, 2007). GTR has also proven relevant in the context of changing reporting systems, accounting digitalization, and the integration of sustainability principles such as ESG, where meaning, professional identity, and interpretive processes are dominant elements (Adams & Larrinaga, 2019). The study's findings confirm that GTR not only offers a systematic method for data collection and analysis, but also provides a more reflective, context-sensitive epistemological framework capable of generating substantive theory that is truly rooted in organizational reality. Thus, GTR is a powerful methodological alternative in enriching accounting knowledge, while providing a deeper understanding of how accounting practices are executed, negotiated, and interpreted in everyday organizational life.